Em que espelho ficou perdida a minha face? : uma análise da condição da mulher nas Obras do cárcere de Antonio Gramsci - Mendes, Gigliola (2013)
This research aims to discuss the woman condition on the capitalist system which has the patriarchal model of society as one of his foundations as well as analyzing how this question is bonded to the fight for society s transformation. Therefore, the reflection proposes to situate the woman question inside the context of the class struggle, opting for analyzing, not in the perspective of the feminist conceptions, but of the Philosophy of Praxis of Antonio Gramsci. This option is justified considering that the philosopher, despite of his ambiguous thought regarding the woman condition, introduces in his Prison Works a relevant reflection concerning the theme. Such reflection points the origins of the peculiar feminine subalternity, which prolongs itself in the capitalism, and the necessity of forming a new feminine personality as a part of the intellectual and moral reform constructed by organic intellectuals of the working class , with the purpose of overcoming the burgess hegemony, in order to build one nuova civiltà. Therefore, we will look forward to investigate this philosopher s demand for the development of a new feminine personality, in order to comprehend if, by his categories, it is possible to think about the emancipation and the liberation of the women in the context of capitalism or if it is anticipated a limited role for woman on this process, which she would simply had to adequate herself to the claims of the working class, submitting again herself to a pedagogic relation with men, without having an action room to overcome the peculiar obstacles for his gender in search of her autonomy.